Mitochondria-targeted ratiometric fluorescent probe for real time monitoring of pH in living cells - Wu, Ming-Yu; Li, Kun; Liu, Yan-Hong; Yu, Kang-Kang; Xie, Yong-Mei; Zhou, Xue-Dong; Yu, Xiao-Qi (Biomaterials, 2015)
Pyridinium functioned 7-hydroxy coumarin was presented as the first mitochondria-targeted ratiometric fluorescent probe CP for real time monitoring pH in living cells. Compared with commercially available mitochondrial trackers, CP possesses high specificity to mitochondria in living cells as well as good biocompatibility. Meanwhile, CP displays excellent pH sensitivity and anti-interference capability. Confocal image experiments confirm that CP can monitor mitochondrial pH changes associated with the mitochondrial acidification, cellular apoptosis and stress response efficiently in real time.